2017
DOI: 10.1073/pnas.1613193114
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is projected to have severe impacts on the frequency and intensity of peak electricity demand across the United States

Abstract: The empirical literature has shown significant increases in climate-driven impacts on overall consumption, yet has not focused on the cost implications of the increased intensity and frequency of extreme events driving peak demand, which is the highest load observed in a period. We use comprehensive, high-frequency data at the level of load balancing authorities to parameterize the relationship between average or peak electricity demand and temperature for a major economy. Using statistical models, we analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(207 citation statements)
references
References 17 publications
10
180
2
1
Order By: Relevance
“…. , 6 to capture the influence of other influencing factors that operate on lower frequencies than electricity demand, such as macroeconomic activity (32,(54)(55)(56). Recursively, the Chebyshev polynomials are given by …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. , 6 to capture the influence of other influencing factors that operate on lower frequencies than electricity demand, such as macroeconomic activity (32,(54)(55)(56). Recursively, the Chebyshev polynomials are given by …”
Section: Methodsmentioning
confidence: 99%
“…33 and 34). Furthermore, most prior studies examined total consumption impacts, whereas recent results suggest that the effects on peak load (i.e., the highest load observed in a day/ month/year) may be substantially larger and costlier (32). This study uses observed hourly electricity data across 35 European countries-which are connected by the world's largest synchronous electrical grid-to estimate how climate change impacts the intensity of peak-load events and overall electricity consumption.…”
mentioning
confidence: 99%
“…Large backup facilities are needed to guarantee a stable supply of electricity during periods of low wind and solar power generation . Furthermore, climate change affects the demand for electric power (Auffhammer et al, 2017) as well as the operation conditions for thermoelectric and hydroelectric power plants which serve as backup (van Vliet et al, 2016(van Vliet et al, , 2012. However, feedback effects of largescale wind fleets on atmospheric flows are limited .…”
Section: Introductionmentioning
confidence: 99%
“…Specific to the context of thermostats, we extend existing studies on climate adaptation (e.g., Auffhammer et al 2017;Carleton and Hsiang 2016;Deschenes and Greenstone 2011) with more fine-grained analysis of how our energy use patterns will respond to outdoor temperature changes. In particular, recent climate science (e.g., Lewis and King 2017) has emphasized that climate change will not only change mean temperatures, but also affect the variability of weather patterns as well.…”
Section: Discussionmentioning
confidence: 99%